Interactive assistance for teaching C++ array topic to novice learners / Naemah Abdul Wahab, Jamal Othman and Saiful Nizam Warris - Abdul Wahab, Naemah; Othman, Jamal; Warris, Saiful Nizam (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2016)
Previous research has suggested that teaching and learning computer programming to novice learners; particularly engineering students is a very challenging task. The complex nature of programming subject, lack of problem solving skills and misunderstanding of programming syntax and semantics are a few of the possible reasons of learner’s negative stereotypes and difficulties with programming subject. Many researchers found that engineering students can be categorized under the “visual learner” side of the Felder-Silverman Learning Styles Model. However, the mismatches that exist between the learner’s learning styles and traditional text-based programming language and auditory teaching approach contribute to misunderstanding, strong dislike and poor performance of students in programming subject. As programming novices prefer to comprehend visually, this study investigates the effectiveness of using interactive teaching aid as a tool in improving programming understanding specifically designed for novice learners, focused only in array topic in C++ introductory course. Initial results show that the learning performance and program comprehension on array C++ topic improved after using the teaching aid.